Implementasi Kebijakan E-government Terhadap Moral Kerja dan Implikasinya pada Kinerja Pegawai di Jajaran Pemerintah Aceh - Anugrah Diansyah; Irma Farnita (Jurnal EMT KITA, 2021)
This study aims to analyze the implementation of e-government policies in SKPD within the Aceh Government and their impact on employee performance. Considering that work morale can also be an important determinant of performance formation, in this study employee morale is used as an intermediary variable between employee performance and the implementation of e-government policies. The research uses a quantitative approach with a causal design that examines the functional relationship between employee performance and the implementation of e-government and work morale. The unit of analysis is 47 SKPD in the ranks of the Aceh Government. Research respondents in each SKPD as many as 5 people so that the total respondents are 235 employees. Collecting data using a questionnaire distributed to employees in each SKPD. The questionnaire contains questions related to employee performance, e-government policies, and works morale. Each statement provided alternative answer choices in the form of a level of agreement ranging from strongly disagree, disagree, disagree, agree, and strongly agree. Each answer choice is given a score based on a Likert scale with a weight of 1 to 5. In order to test the functional relationship between variables, the AMOS 21 statistical inference model structural equation model (SEM) is used. This is done through efforts to improve the quality of e-government implementation and strengthen employee morale. Each SKPD head should pay attention to the importance of improving the quality of e-government which has been implemented so far in improving the quality of public services. Along with the development of information and communication technology, the implementation of e-government needs to be balanced with innovation in the field of public services. Besides being able to have an impact on improving the work of carrying out tasks by employees, service innovations supported by e-government will have a good impact on the quality of services for the communityÂ